Transfeminist Manifesto - Koyama, Emi (eminism.org, 2001)
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; identités LGBTQIA2+; manifeste; militance; premier cycle; ressource en ligne; régions géographiques; sex3383; thématiques; transféminisme; états-unis

Intersex Initiative: From "Intersex" to "DSD" - Koyama, Emi (2006)
keynote speech presented at Translating Identity conference held at University of Vermont in February 2006.
Keywords: EDI; LGBTQIA2+; approches et analyses; capacitisme; cours; discipline; intersexuation; patriarcat; premier cycle; queer; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

From Social Construction to Social Justice: Transforming How We Teach about Intersexuality - Koyama, Emi; Weasel, Lisa (Women's Studies Quarterly, 2002)
Keywords: LGBTQIA2+; approches et analyses; capacitisme; corps; cours; discipline; intersexuation; justice sociale; premier cycle; pédagogie; santé; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap